2022
DOI: 10.3389/fmicb.2022.889415
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Colonization and Immune Landscapes of Periodontitis Microbiota in Germ-Free Mice With Streptozotocin-Induced Type 1 Diabetes Mellitus

Abstract: A two-way relationship between diabetes and periodontitis has been discussed recently. Periodontitis microbiota might affect the immune homeostasis of diabetes, but the molecular mechanism of their interactions is still not clear. The aims of this study were to clarify the possible immune regulatory effects of periodontitis microbiota on diabetes and the correlation between immunomodulation and ectopic colonization. A model of germ-free mice with streptozotocin-induced type 1 diabetes mellitus (T1D), which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Depleting gut microbiota or transplanting healthy gut microbiota after induction of periodontitis could decrease insulin resistance, indicating that the gut microbiota may mediate the influence of periodontitis on prediabetes [ 16 ]. Another study demonstrated that saliva of periodontitis patients could not increase insulin resistance in diabetes germ-free mice, suggesting the important role of gut microbiota in mediating the influence of oral microbiota on diabetes [ 72 ].…”
Section: Oral Microbiota Gut Microbiota and Systemic Diseasesmentioning
confidence: 99%
“…Depleting gut microbiota or transplanting healthy gut microbiota after induction of periodontitis could decrease insulin resistance, indicating that the gut microbiota may mediate the influence of periodontitis on prediabetes [ 16 ]. Another study demonstrated that saliva of periodontitis patients could not increase insulin resistance in diabetes germ-free mice, suggesting the important role of gut microbiota in mediating the influence of oral microbiota on diabetes [ 72 ].…”
Section: Oral Microbiota Gut Microbiota and Systemic Diseasesmentioning
confidence: 99%